Genome-wide association study reveals three susceptibility loci for common migraine in the general population - Chasman, Daniel I; Schürks, Markus; Anttila, Verneri; de Vries, Boukje; Schminke, Ulf; Launer, Lenore J; Terwindt, Gisela M; van den Maagdenberg, Arn M J M; Fendrich, Konstanze; Völzke, Henry; Ernst, Florian; Griffiths, Lyn R; et al. (Nature genetics, 2011)
Markus Schürks and colleagues report a genome-wide association study for common migraine. They identify three new susceptibility loci at PRDM16 , TRPM8 and LRP1 . Migraine is a common, heterogeneous and heritable neurological disorder. Its pathophysiology is incompletely understood, and its genetic influences at the population level are unknown. In a population-based genome-wide analysis including 5,122 migraineurs and 18,108 non-migraineurs, rs2651899 (1p36.32, PRDM16 ), rs10166942 (2q37.1, TRPM8 ) and rs11172113 (12q13.3, LRP1 ) were among the top seven associations ( P < 5 × 10 −6 ) with migraine. These SNPs were significant in a meta-analysis among three replication cohorts and met genome-wide significance in a meta-analysis combining the discovery and replication cohorts (rs2651899, odds ratio (OR) = 1.11, P = 3.8 × 10 −9 ; rs10166942, OR = 0.85, P = 5.5 × 10 −12 ; and rs11172113, OR = 0.90, P = 4.3 × 10 −9 ). The associations at rs2651899 and rs10166942 were specific for migraine compared with non-migraine headache. None of the three SNP associations was preferential for migraine with aura or without aura, nor were any associations specific for migraine features. TRPM8 has been the focus of neuropathic pain models, whereas LRP1 modulates neuronal glutamate signaling, plausibly linking both genes to migraine pathophysiology.